PENGEMBANGAN PROGRAM PENDIDIKAN KARAKTER UNTUK MENGATASI PERUNDUNGAN DI LINGKUNGAN PENDIDIKAN - Susilawati, Leli; Permana, Yan yan Yoga; Nugraha, Cepi; Wasliman, Eva Dianawati (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This research was prepared with the aim of examining in more depth how the character education program developed at Madrasah Tsanawiyah PPI 165 Arjasari was to overcome student bullying which often occurs in the madrasa environment and what results were achieved by the madrasah in its program development efforts. It is hoped that the results of this research can be useful for author and becomes a reference for other madrasas in their efforts to develop character education programs in their schools. The author in this research used a descriptive method to solve problems that occurred, in the form of actual problems. The data collected and compiled is explained up to the analysis stage in the form of observations, interviews and documentation studies. The results of the program implemented in this madrasa are able to minimize cases of bullying that have occurred before and are more developed so as to produce an output of madrasa students who respect each other and respect each other, because Madrasah Tsanawiyah PPI 165 has its own way of implementing it, among the programs developed consists of 4 aspects, namely understanding morals, special formation, habituation and the allegiance ceremony